THE INFLUENCE OF WORK SAFETY CULTURE AND WORK SAFETY MONITORING SYSTEM ON WORK SAFETY - Tita Latifah Ahmad; Hanin Fitria; Cikita Berlian Hakim (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2022)
In building construction, there are many things that must be considered, one of which is work safety due to construction industry is a highly hazardous environment. Early signs of an organization's commitment to safety policies are manifested in the safety culture of the organization. Improving contractor safety culture can reduce work accidents on construction industry projects. It is unclear how to improve safety culture among construction industries, practically. The purpose of this study was to analyze the influence of safety culture and its association with management commitment in monitoring system of work safety. Structural Equation Modeling (SEM) method was used by researchers in testing the relationship between the measured variables and the latent construct. According to the results of this study, it can be concluded that Work Safety Culture (X1) has an influence on Work Safety (Y) based on the t-value of 2.721 ≥ 1.64, Work Safety Culture (X1) has an influence on the Work Safety Monitoring System (X2) that verified with a t-value of 3.772, Work Safety Monitoring System (X2) has no effect on Work Safety (Y) based on a t-value of 1.195 < 1.64, and Work Safety Culture (X1) has no influence on Work Safety (Y) through the Work Safety Monitoring System (X2) with a t-value of 0,877. The results of this study can be used as the basis for implementing a safety culture in the company because it is proven to have an important role in work safety so that it is expected to reduce work accidents with the support of management who are committed to consistently carrying out work safety monitoring systems.